THE DEFECT AND PROJECT RULES INSPECTION ON PCB LAYOUT IMAGE - Doudkin, Alexander; Inyutin, Alexander (International Journal of Computing, 2014)
A technique of PCB layout optical inspection based on image comparison and mathematical morphology methods is proposed. The unique feature of the technique is that the inspection is performed at different stages of image processing. The presence of all layout elements is checked up, then positions of found elements and their conformity to project rules are verified, the breakouts and shorts are found. The inspection of mousebits, spur and pinholes on conductors is also carried out.